Executive Functions in Insomnia Disorder: A Systematic Review and Exploratory Meta-Analysis - Ballesio, Andrea; Aquino, Maria Raisa Jessica V.; Kyle, Simon D.; Ferlazzo, Fabio; Lombardo, Caterina (Frontiers in Psychology, 2019)
Background: Executive functions (EFs) are involved in the control of basic psychological processes such as attention and memory and also contribute to emotion regulation. Research on the presence of EFs impairments in insomnia yielded inconsistent results. Therefore, we performed a systematic review of the literature on three EFs: inhibitory control, working memory and cognitive flexibility in adults with insomnia in order to investigate the presence and magnitude of insomnia-related EFs impairments. Methods: PubMed, Scopus, Medline and PsycINFO were searched. Risk of bias assessment of included studies was performed by two independent researchers. Findings were summarised using both a narrative approach and meta-analysis. Cohen’s d was calculated at 95% confidence interval (CI) as effect size of between groups differences. Results: Twenty-eight studies comparing adult individuals with a diagnosis of insomnia and healthy controls on neuropsychological measures of EFs were included. Narrative synthesis revealed substantial variability across study findings. Factors that were primarily hypothesised to account for this variability are: objective sleep impairments and test sensitivity. Exploratory meta-analysis showed impaired performance of small to moderate magnitude in individuals with insomnia as compared to controls in reaction times, but not accuracy rates, of inhibitory control (d= -.32, 95% CI: -.52 - -.13) and cognitive flexibility tasks (d=-.30, 95% CI: -.59 - -.01). Performance in working memory tasks was also significantly impacted (d=-.19, 95% CI: -.38 - -.00). Effects sizes were larger when insomnia was associated with objective sleep impairments, rather than normal sleep. Conclusions: We gathered evidence supporting small to moderate deficits in EFs in individuals with insomnia. Due to the small sample size results should be considered preliminary and interpreted carefully.